2020
DOI: 10.1039/d0ra07114e
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ordered macroporous ZIF-8 nanoparticle-derived nitrogen-doped hierarchical porous carbons for high-performance lithium–sulfur batteries

Abstract: Lithium–sulfur (Li–S) batteries have attracted considerable attention due to their ultra-high specific capacity and energy density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For short‐chain sulfur–carbon hosts, heteroatom doping can be easily introduced into the carbon hosts during the carbonization process of the precursors. Most commonly, nitrogen doping in ZIF‐derived MPCs is studied in both Li and Na–S systems due to the nitrogen‐containing imidazolate, resulting in significant nitrogen doping in the derived carbon hosts 53,54,67 . Due to their high electronegativity and small atomic diameter, nitrogen atoms are able to improve battery performance by binding to sulfur species and facilitating sulfur immobilization 59,68,69 .…”
Section: Short‐chain Sulfur Via Physical Confinementmentioning
confidence: 99%
See 1 more Smart Citation
“…For short‐chain sulfur–carbon hosts, heteroatom doping can be easily introduced into the carbon hosts during the carbonization process of the precursors. Most commonly, nitrogen doping in ZIF‐derived MPCs is studied in both Li and Na–S systems due to the nitrogen‐containing imidazolate, resulting in significant nitrogen doping in the derived carbon hosts 53,54,67 . Due to their high electronegativity and small atomic diameter, nitrogen atoms are able to improve battery performance by binding to sulfur species and facilitating sulfur immobilization 59,68,69 .…”
Section: Short‐chain Sulfur Via Physical Confinementmentioning
confidence: 99%
“…Most commonly, nitrogen doping in ZIF-derived MPCs is studied in both Li and Na-S systems due to the nitrogen-containing imidazolate, resulting in significant nitrogen doping in the derived carbon hosts. 53,54,67 Due to their high electronegativity and small atomic diameter, nitrogen atoms are able to improve battery performance by binding to sulfur species and facilitating sulfur immobilization. 59,68,69 For the ZIF-8derived MPC cathodes reported by Eng et al, higher nitrogen doping was found to lead to superior long-term cycling stability and Coulombic efficiency despite having lower electrical conductivity and reaction kinetics.…”
Section: Doping Of Host Structuresmentioning
confidence: 99%
“…[92,93] Under the synergetic effects of these advantages, high mass loading electrodes with hierarchical structures have become much popular, which are usually fabricated by ball-milling method, hydrothermal method, selfassembly technique, and template approach. [94][95][96] Among these methods, template approach is widely used to construct hierarchical structures, including hard and soft templates approach. Hard template approach usually adopts rigid or semirigid materials (often ZnO, TiO 2 , etc) as mold to support the precursor materials, and then etching the inner template to achieve hierarchical structures.…”
Section: Hierarchical Structuresmentioning
confidence: 99%
“…Compared to traditional porous materials, they possess unique advantages, including a strong periodicity of the pore structure arrangement, a narrow pore size distribution, uniform adjustment within a certain range, and optimal mass transfer [ 26 ]. Consequently, 3DOM materials are widely utilized in catalysis, separation, the environment, sensors, and batteries [ 27 , 28 , 29 , 30 , 31 ]. However, until now, most 3DOM materials have been prepared in the form of thin films or block monomers [ 31 , 32 , 33 , 34 ], and there has been little research on the preparation of spherical 3DOM materials, which has limited the development of these materials in the field of high-efficiency separation and adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, 3DOM materials are widely utilized in catalysis, separation, the environment, sensors, and batteries [ 27 , 28 , 29 , 30 , 31 ]. However, until now, most 3DOM materials have been prepared in the form of thin films or block monomers [ 31 , 32 , 33 , 34 ], and there has been little research on the preparation of spherical 3DOM materials, which has limited the development of these materials in the field of high-efficiency separation and adsorption.…”
Section: Introductionmentioning
confidence: 99%